Interprofessional spiritual care in oncology: a literature review - Puchalski, Christina M (ESMO Open, 2019)
Spiritual care is recognised as an essential element of the care of patients with serious illness such as cancer. Spiritual distress can result in poorer health outcomes including quality of life. The American Society of Clinical Oncology and other organisations recommend addressing spiritual needs in the clinical setting. This paper reviews the literature findings and proposes recommendations for interprofessional spiritual care.